Civilian Conservation Corps, Company 2762, Camp Partridge River F-52, near Allen (Iron Range Research Center, 1005 Discovery Drive, Chisholm, Minnesota 55719; http://mndiscoverycenter.com/research-center)
461ea1cf95cb618919b4d8bfa02692c9
United States
Minnesota
St. Louis
Allen Township
461ea1cf95cb618919b4d8bfa02692c9
Keywords: Allen, MN; CCC: Civilian Conservation Corps, Co. 2767, Project F-52; Group portraits; Camps; Public service employment; Civil service; Civilian Conservation Corps (U.S.); Social issues